Between-Session Reliability of Common Strength- and Power-Related Measures in Adolescent Athletes - Christopher Thomas; Thomas Dos'Santos; Paul Comfort; Paul A. Jones (MDPI AG, 2017)
The purpose of this study was to investigate the between-session reliability of common strength- and power-related measures in adolescent athletes. Seventeen adolescent athletes (males: n = 8: age 17.1 ± 2.2 years; height 175.6 ± 3.5 cm; mass 80.2 ± 3.6 kg; females: n = 9; age 16.9 ± 2.6 years; height 178.5 ± 4.3 cm; mass 71.5 ± 4.5 kg) participated in this study. Isokinetic dynamometry, isometric mid-thigh pull (IMTP), countermovement jump (CMJ), and horizontal jumps (standing broad jump (SBJ) and single-leg hop (SLH)) were each performed twice on separate days, seven days apart. Reliability was assessed by intraclass correlation coefficient (ICC), coefficient of variation (%CV), standard error of measurement (SEM), and smallest detectable difference (SDD). Intraclass correlation coefficients and CV demonstrated acceptable between-session reliability for all measures (ICC > 0.63; CV < 11%), except rate of force development and impulse measures during bilateral and unilateral stance IMTP. Smallest detectable differences demonstrated that changes in performance of >7% CMJ height, >8% SLH distance, >10% in peak isometric force, and >5% in isokinetic peak torques should be considered meaningful, when assessing adolescent athletes.